Phosphorus contribution to improving quality in Lilium and its relationship with Glomus fasciculatum and Bacillus subtilis - Rubí Arriaga Martín; González Huerta Andrés; Olalde Portugal Víctor; Reyes Reyes, Basilio Gabriel; Castillo González Ana María; Pérez López Delfina de Jesús; Aguilera Gómez Luis Isaac (Revista Mexicana de Ciencias Agrícolas, 2018)
Lilium sp. is among the most important species in the production of cut-flowers in Mexico, but its cultivation is based on the use of significant amounts of chemical fertilizers, so it is desirable to minimize the impact on the ecosystem without compromising the product quality. This study was conducted to evaluate the main effects and interactions of phosphorus, Glomus fasciculatum and Bacillus subtilis, on the commercial quality of flowers of Lilium oriental hybrid Showwinner under greenhouse conditions. In two consecutive cycles between 2007 and 2008, 12 treatments in a factorial arrangement 2*3*2 were studied using analysis of variance, comparing treatment means with the test of least significant difference (LSD, p = 0.05) and main component analysis. G. fasciculatum, 22 μg ml-1 of phosphorus and B. subtilis were positively correlated with root dry weight, plant height, stem dry weight, petal width, f lower diameter, f lower dry weight, life of the f lower, f lowering time and concentration in the stems of zinc (Zn), copper (Cu), potassium (K), nitrogen (N), phosphorus (P) and calcium (Ca). These results show that the rhizosphere microorganisms used, may interact positively to promote growth and development of the plant and improve the quality of Lilium sp. with 22 μg ml-1 of phosphorus.